Distinct Histologic, Immunohistochemical and Clinical Features Associated With Serous Endometrial Intraepithelial Carcinoma Involving Polyps. (March 2020) - Trinh, Vincent Q.-H.; Pelletier, Mathieu P.; Echelard, Philippe; Warkus, Thomas; Sauthier, Philippe; Gougeon, François; Mès-Masson, Anne-Marie; Provencher, Diane M.; Rahimi, Kurosh
Abstract : The origin of serous endometrial intraepithelial carcinoma (SEIC) is debated, due to its premalignant and independently malignant nature. It often arises next to endometrial serous carcinoma (ESC), with a propensity for polypoid growth. We aimed to better characterize this discrepancy by analyzing the clinical, histologic, and immunohistochemical features of polypoid carcinoma associated with SEIC (P-SEIC), and compared them with usual endometrial serous carcinoma without SEIC (UESC). Consecutive patients with P-SEIC were recruited and compared with UESC controls from our institutional research center. Clinical, histologic, and immunohistochemical (IHC, ER, PR, P53, Napsin-A, WT1, P16) were analyzed. BRCA testing results and familial history were also extracted from clinical databases. Welch T test, Pearson χ 2, and Fisher exact test were performed in SPSS version 23. A total of 37 P-SEIC and 25 UESC were the basis of a case-control study. P-SEIC was associated with more bilateral ovarian involvement ( P =0.026), yet showed lower rates of myometrial invasion ( P =0.002). P-SEIC showed a statistically different IHC profile: p53+, p16+, ER+, PR+, and WT-1+, and high rates of Napsin-A, while UESC was p53+, p16+, WT-1−, Napsin-A−, with lower rates of ER and PR. We also identified 2 patients who received prophylactic salpingo-oophorectomy for BRCA mutations and who subsequently developed P-SEIC with its unique IHC pattern. Our results suggest different underlying expression profiles and possibly diverging molecular signatures between both P-SEIC and UESC. If confirmed in further molecular studies, it could lead to a distinct molecular subclass.